The Role of Compensation in Enhancing Employee Productivity and Performance: An Islamic Economic Perspective - Nurut Tamam (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to analyze the role of compensation in improving employee performance productivity from the perspective of Islamic economics. This research uses a qualitative approach with a literature review method by examining various scientific sources, including journals, books, and relevant previous studies. The data were analyzed descriptively to identify patterns and relationships between compensation and employee productivity. The results show that compensation has a significant role in improving employee productivity through increased motivation, job satisfaction, and work loyalty. Fair and appropriate compensation, both financial and non-financial, contributes to enhancing work performance and organizational efficiency. From the perspective of Islamic economics, compensation must be based on principles of justice (‘adl), feasibility, and timeliness, as emphasized in the Qur'an and Hadith. Proper implementation of compensation not only improves employee welfare but also supports sustainable organizational performance.